Réponses

2014-02-13T19:53:47+01:00
(a)

A pour a =1 et b=5 ;

A = 1/4 [ (a + b )² - ( a - b )² ]
A = 1/4 [ ( 1 + 5 )² - ( 1 - 5 )² ]
A = 1/4 [ 6² - (-4)² ]
A = 1/4 [ 6² + 4² ]
A = 1/4 ( 36 + 16 )
A = 1/4 x 52 
A = 13

A pour a= -2 et b= -3 :

A = 1/4 [ (a + b )² - ( a - b )² ]
A = 1/4 [ ( -2 -3 )² - ( -2 +3 )² ]
A = 1/4 [ (-5)² - (1)² ]
A = 1/4 ( 25 - 1 )
A = 1/4 x 24
A = 6

(B) 

A pour a =1 et b=5 ;

1 x 5 = 5

A pour a= -2 et b= -3 :

(-2) x (-3) = 6

Alors , Alex il n'a pas raison, parce que a * b ≠ toujours le numéro A